Matrices insumo-producto regionales: Una aplicación al sector automotriz en México - Leonardo Egidio Torre Cepeda; Jorge A . Alvarado Ruiz; Miroslava Quiroga Trevi\~no (Banco de México, 2017)
– We use the national Input-Output Matrix 2012 of INEGI and Flegg's approach to estimate four Regional Input-Output Matrices (RIOM) applying Banco de Mexico's regionalization. The RIOM are employed to evaluate the effects on gross output, value added and employment at the regional level resulting from two shocks: (a) the construction of a hypothetical automotive plant worth 1,000 million dollars; and (b) the production of 200,000 vehicles per year in that plant. The exercise reveals that: (i) the construction and the operation of the plant at full capacity have differentiated effects across regions and sectors on the studied variables, in both absolute and relative terms; (ii) the spillover effects resulting of both shocks within each region are concentrated in a limited number of sectors; and (iii) the north central region resulted to be the one receiving the largest relative benefits from both shocks.
Keywords: R11; R12; R15; 330; Input-Output Model; Regional Analysis; Multiplier Effects; Automotive Sector